The rise of the national monetary system of the People’s Republic of Tuva (1921–1944) - Harunova Marianna М.-B.; Harunov, Ramil Sh. (The New Research of Tuva, 2019)
The article examines a complex process of setting up the national monetary system of Tuva in 1930s-1940s and is based on the existing scholarly research, and the authors’ work on museum collections and archival records available in the Republic of Tuva. One of the priority tasks of the People’s Republic of Tuva, a state founded in 1921, was to develop a financial system of its own. The republic had to deal with the situation when currencies of several countries were in simultaneous circulation in the region since the turn of twentieth century. The help of the USSR made it possible to carry out a monetary reform, which was implemented in several stages. The transitional period, which lasted from 1921 to 1935, witnessed a simultaneous use of Chinese liangs, Mongolian tögrögs, rubles of both pre-revolution Russian Empire and the Soviet Union as monetary units. Between 1935 and 1940, the republic adopted its own national currency, the aksha (banknotes were issued in 1935 and in 1940). These measures contributed to the further economic development of the People’s Republic of Tuva and helped create its national budget, a fiscal system and other financial institutions, without which the rise of the young state would have been impossible, as well as social, economic and cultural transformations that contributed to a shift to advanced mixed economy.